The ABC of crop insurance as a risk management tool: A manual for trainers - Murabula, Sarah; Hientz, Lennart; Binge, Brenda; Mwongera, Caroline; Muriithi, Cyrus K; Kinyua, Ivy Wambui; Osiemo, Jamleck (2023)
This manual is a product of the Alliance of Bioversity International and International Center for Tropical Agriculture (CIAT), and the University of Kassel, as part of the outputs of the Innovation for Africa Climate Risk Insurance (InACRI) project funded by the German Federal Ministry of Education and Research (BMBF). The InACRI project addresses the current poor performance and uptake of index-based crop insurance products in Kenya. As part of the outputs to improve adoption the project developed a trainer’s guide to demystify concepts on crop insurance and elaborate its role as a risk management strategy at a technical level. The manual incorporates new concepts and innovations not in existing manuals. The manual is to be used by trainers of crop insurance, extensionists working on crop insurance, champion farmers, and anyone working on agricultural risk and agricultural risk management.